Monitoring of indicators and criteria for assessing energy consumption by residential buildings - PEREGINETS , Ivan (Ways to Improve Construction Efficiency, 2024)
The scientific article reveals the role of monitoring energy consumption by residential real estate objects throughout the life cycle, which is an integral part of increasing energy efficiency. An analysis of the existing methodology for assessing the energy efficiency of real estate construction has been conducted. Promising concepts of methods for assessing indicators and criteria for the energy needs of buildings while ensuring comfortable conditions for people to stay in them have been investigated. Studies indicate that the use of a system for continuous monitoring of energy consumption indicators according to energy efficiency criteria provides significant resource savings with a reduction in maintenance costs and operating costs. The prospects for implementing monitoring of energy efficiency indicators are substantiated. The feasibility of an integrated approach to monitoring indicators and criteria for assessing energy consumption, including all stages of the life cycle of buildings and structures, has been proven. The methodology proposed by the author of the article can be applied by an individual energy manager and energy management departments of municipal enterprises, managers of multi-apartment residential buildings. Considerable attention in energy management work is paid to the collection and analysis of data on the consumption of fuel and energy resources in buildings and structures of the municipal and budgetary sphere, including dormitories of educational institutions of various degrees of accreditation. At the same time, investors and managers of residential buildings have the opportunity to ensure: correct operation of equipment; creation of an archive of energy consumption data; identification of methods and means for the greatest increase in energy efficiency potential. The article discloses the use of the "ET-diagram" and "ET-curve" as basic components of monitoring indicators and criteria for assessing energy consumption by residential buildings. Weekly energy monitoring is recommended for timely detection of unforeseen PER costs and elimination of possible malfunctions. The application of the methodology presented in the article is appropriate for both individual residential buildings and complexes of buildings, blocks, neighborhoods and cottage towns with a centralized PER supply system. Based on the research results, the main principles of monitoring energy consumption indicators have been determined, which contribute to increasing the financial and economic indicators of facilities. The proposed approach to organizing monitoring indicators and criteria for assessing energy consumption by residential buildings allows for a thorough analysis of resource consumption and forecasting the volumes of their use for the future, including the use of BIM technologies.